Why Does Energy-Saving Behavior Rise and Fall? A Study on Consumer Face Consciousness in the Chinese Context - Wang, Li; Wei, Feng; Zhang, Xin-an (Journal of business ethics, 2019)
This research examines the effect of an individual difference variable that reflects the extent to which one desires positive evaluations from others—that is, face consciousness on consumer energy-saving behavior—as well as the mechanism through which the effect occurs and conditions under which it varies. Drawing upon the means-end theory of lifestyles, we propose that face consciousness increases a status-seeking lifestyle and thus decreases energy-saving behavior. Moreover, the negative relationship between status-seeking lifestyle and energy-saving behavior is contingent upon a perceived seriousness of environmental problems and perceived environmental responsibility, such that the indirect and negative effect of such face consciousness is stronger for consumers who perceive less serious environmental problems and less environmental responsibility. Results from an experimental study and a field study using samples of Chinese consumers provide consistent evidence for the hypothesized model. Theoretical and practical implications for energy-saving behavior are also discussed.